The Development of Students’ Worksheet on Students’ Creative Thinking Skill - Abdul Bashith; Saiful Amin; Ravinesh Rohit Prasad; De Nanda Mei Dwi Kidzikri (AT-TA'LIM, 2019)
This study aims to 1) explain the development products of Student Worksheet on Student's creative thinking Skill; 2) describe the validity product of student Worksheet on Student's creative thinking Skill; and 3) describe the influence of student worksheet on Student's creative thinking Skill. The method in this study used to research and development (RD) the model of R D in this study using Borg Gall. The analysis used in the study of development technique has three of them, a review of the learning contents, descriptive analysis, and the analysis of the test results. The development of learning materials in the form of student worksheet of creativity proved can improve the process creative thinking skill of grade V SDN Tambak Asri 02 Malang. Suggestions for optimizing the utilization of materials development is 1) the development of learning materials can utilized as references for educators. 2) Learning materials that have been developed this for more good news can be integrated with the Quran or the Hadith perspective.